Sex Differences in Salience Network Connectivity and its Relationship to Sensory Over‐Responsivity in Youth with Autism Spectrum Disorder. Issue 9 (28th August 2020) - Cummings, Kaitlin K.; Lawrence, Katherine E.; Hernandez, Leanna M.; Wood, Emily T.; Bookheimer, Susan Y.; Dapretto, Mirella; Green, Shulamite A.
Abstract: Individuals with autism spectrum disorder (ASD) are significantly more likely to experience sensory over‐responsivity (SOR) compared to neurotypical controls. SOR in autism has been shown to be related to atypical functional connectivity in the salience network (SN), a brain network thought to help direct attention to the most relevant stimuli in one's environment. However, all studies to date which have examined the neurobiological basis of sensory processing in ASD have used primarily male samples so little is known about sex differences in the neural processing of sensory information. This study examined the relationship between SOR and resting‐state functional connectivity in the SN for 37 males and 16 females with autism, ages 8–17 years. While there were no sex differences in parent‐rated SOR symptoms, there were significant sex differences in how SOR related to SN connectivity. Relative to females with ASD, males with ASD showed a stronger association between SOR and increased connectivity between the salience and primary sensory networks, suggesting increased allocation to sensory information. Conversely, for females with ASD, SOR was more strongly related to increased connectivity between the SN and prefrontal cortex. Results suggest that the underlying mechanisms of SOR in ASD are sex specific, providing insight into the differences seen in the diagnosis rate and symptom profiles of males and females with ASD. Lay Summary: Sensory over‐responsivity (SOR) is common in autism. Most research on the neural basis of SOR has focused on males, so little is known about SOR or its neurobiology in females with autism spectrum disorder. Here despite no sex differences in SOR symptoms, we found sex differences in how SOR related to intrinsic connectivity in a salience detection network. Results show sex differences in the neural mechanisms underlying SOR and inform sex differences seen in diagnosis rates and symptom profiles in autism. Autism Res 2020, 13: 1489–1500 . © 2020 International Society for Autism Research, Wiley Periodicals, Inc.